Effects of visual feedback on bimanual force control capabilities and motor unit activation patterns - Lee, H.; Ko, D.-K.; Kang, N. (Korean Journal of Sport Biomechanics, 2025)
Objective: The purpose of this study was to investigate effects of visual feedback on bimanual force control and motor unit discharge patterns in healthy young adults.